ANALISIS NILAI TAMBAH PENANGANAN PASCA PANEN HASIL PRODUKSI HIDROPONIK SELADA (Lactuca sativa L) DI KEBUN BERTANI AGRO FARM - Ridwan, Awaludin; Maulidah, Afsah Indah; Setyaningsih, Setyaningsih (Agros Journal of Agriculture Science, 2024)
Lettuce is one type of vegetable plant that is widely consumed by the community because lettuce has high nutritional content and good economic and agribusiness potential. Agricultural products, especially vegetables, are easily damaged. Damage to agricultural products can occur starting from the producer/farmer level, due to harvest and post-harvest handling. Analysis of the added value of post-harvest handling of hydroponic lettuce at Kebun Bertani Agro Farm aims to 1) describe the post-harvest handling of hydroponic lettuce at Kebun Bertani Agro Farm. 2) analyze the amount of added value due to post-harvest handling of hydroponic lettuce at Kebun Bertani Agro Farm. Data were collected using interview and observation methods using the hayami method. The results of this study are 1) Post-harvest handling carried out at the Bertani Agro Farm garden includes sorting, trimming, grading, weighing, packaging, and shipping. 2) The added value of post-harvest handling of hydroponic lettuce obtained was IDR 7,615.83,700 with a ratio of 42.31 percent.